Imaging of Myocardial Ischemia–Reperfusion Injury Using Sodium [F]Fluoride Positron Emission Tomography/Computed Tomography in Rats and Humans - Hongyoon Choi MD, PhD; Jeong Hee Han PhD; Sue Yeon Lim MS; Inki Lee MD; Young-Seok Cho MD, PhD; Eun Ju Chun MD, PhD; Won Woo Lee MD, PhD (Molecular Imaging)
Positron emission tomography (PET)/computed tomography (CT) using sodium [ 18 F]fluoride (Na[ 18 F]F) has been proven to be a promising hot-spot imaging modality for myocardial infarction (MI). We investigated Na[ 18 F]F uptake in ischemia–reperfusion injury (IRI) of rats and humans. Sodium [ 18 F]fluoride PET/CT was performed in Sprague-Dawley rats that had IRI surgery, and it readily demonstrated prominent Na[ 18 F]F uptake in the infarct area post-IRI. Sodium [ 18 F]fluoride uptake was matched with negative 2,3,5-triphenyl-2 H -tetrazolium chloride staining results, accompanied by myocardial apoptosis and associated with positive calcium staining results. Furthermore, area at risk was negative for Na[ 18 F]F uptake. Cyclosporine A (CysA) treatment reduced standardized uptake value of 18 F over the infarct area, and a significant decrease in infarct size was also observed by the CysA treatment. In humans, Na[ 18 F]F PET/CT readily demonstrated increased Na[ 18 F]F uptake in the 2 patients with MI post-percutaneous coronary intervention. In conclusion, this study sheds light on the potential utility of Na[ 18 F]F PET/CT as a hot-spot imaging modality for myocardial IRI.